Differential Immune Response to Infection and Acute Inflammation Along the Epididymis - Pleuger, Christiane; Silva, Erick José Ramo; Pilatz, Adrian; Bhushan, Sudhanshu; Meinhardt, Andreas (Frontiers in Immunology, 2020)
The epididymis is a tubular structure connecting the vas deferens to the testis. This organ consists of three main regions — caput, corpus and cauda — that face opposing immunological tasks. A means of combating invading pathogens is required in the distally located cauda, where there is a risk of ascending bacterial infections originating from the urethra. Meanwhile, immune tolerance is necessary at the caput, where spermatozoa with immunogenic neo-antigens originate from the testis. Consistently, when challenged with live bacteria or inflammatory stimuli, the cauda elicits a much stronger immune response and inflammatory-inflicted damage than the caput. At the cellular level, a role for diverse and strategically positioned mononuclear phagocytes is emerging. At the mechanistic level, differential expression of immunoprotective and immunomodulatory mediators has been detected between the three main regions of the epididymis. In this review, we summarise the current state of knowledge about region-specific immunological characteristics and unveil possible underlying mechanisms on cellular and molecular levels. Improved understanding of the different immunological microenvironments is the basis for an improved therapy and couselling of patients with epididymal infections.